Systematic significance of achene morphology in Soroseris, Syncalathium and Parasyncalathium (Asteraceae: Cichorieae). (7th May 2013) - Zhang, Jian‐Wen; Boufford, David E.; Sun, Hang
<x xml:space="preserve">Abstract</x> The systematic significance of the morphological structure of achenes in the Himalayan–Tibetan Plateau endemic genera Soroseris, Syncalathium and Parasyncalathium is described and discussed. The achene surface sculpturing of 15 samples representing 13 species of the three genera was investigated using scanning electronic microscopy (SEM) to evaluate inter‐ and intrageneric relationships of the three genera. Characters such as cell arrangement, shape of the epidermis, type of ornamentation of the outer cell wall and degree of wax development are described. The results show that characters such as the shape of the epidermis and the type of ornamentation of the outer cell wall are distinct between the three genera and useful for species‐level classification. Parasyncalathium souliei differs from Syncalathium, in which it has traditionally been placed, in the short, stout beak of the achene and especially in the obscure outline of the epidermal cells and their long acuminate, steeple‐like, end walls. Combined with karyological and molecular data, the differences in achene morphology and sculpturing further support our recognition of Parasyncalathium as distinct from Syncalathium. The achene characters are not only useful for assessing relationships, but are also useful for delimiting species. © 2013 The Linnean Society of London, Botanical Journal of the Linnean Society, 2013, 173, 476–486.